2010
DOI: 10.1111/j.1365-2354.2010.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-synthesis of women's symptoms experience and breast cancer

Abstract: The aim of this paper is to examine the symptom experience of women with breast cancer using meta-synthesis. Women with breast cancer may experience many symptoms resulting from the primary disease and/or treatment of the disease. It is very important the overall symptom experience from the patients' perspective is captured and understood by health professionals. The question developed was 'What is the symptom experience of women with breast cancer from time of diagnosis to completion of treatment'. The meta-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 73 publications
(100 reference statements)
0
36
0
3
Order By: Relevance
“…From the patients' perspective, the acceptance of environmental conditions was connected to their experience of loss of control. Previous studies have stated that loss of control among people with cancer was associated with loss of personal autonomy in decision‐making (Denieffe & Gooney ), ability to cope with environmental features (Vaartio et al . ) and inability to influence one's own situation (Saarnio et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the patients' perspective, the acceptance of environmental conditions was connected to their experience of loss of control. Previous studies have stated that loss of control among people with cancer was associated with loss of personal autonomy in decision‐making (Denieffe & Gooney ), ability to cope with environmental features (Vaartio et al . ) and inability to influence one's own situation (Saarnio et al .…”
Section: Discussionmentioning
confidence: 99%
“…In studies of hospitalized people with cancer challenges concerning personal control were frequently associated with the hospital environment (Vaartio et al . , Denieffe & Gooney , Rotegard et al . , Saarnio et al .…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to the findings the literature. It has been indicated that cancer diagnosis and treatment cause the following psychological problems in women with breast cancer: anxiety, depression, anger, uncertainty about the future, fear of cancer recurrence, body image distortion, fear of losing female identity (Doumit et al, 2010;Denieffe and Gooney, 2011;Cebeci et al, 2012). In the literature, uncertainty and fear of recurrence are stated to be the most challenging experiences that women with breast cancer have in the process of diagnosis and treatment of the disease (Landmark et al, 2001;Doumit et al, 2010;Elmir et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…About 66% of patients with breast cancer suffer from fatigue after diagnosis and extends beyond treatment end [23]. Fatigue is a multidimensional symptom that affects various aspects of life for patients with cancer [24]. A study found a moderate effect of fatigue among patients with breast cancer and significant correlations among fatigue, depression and body image [25].…”
Section: Introductionmentioning
confidence: 99%